Optimization of Alkaline Protease Production by Alkaliphilic Bacillus lehensis G1 using Statistical Design - Aini Sulaiman, Noorul; Kheng Oon, Low; Muhammad Mahadi, Nor; Zazarina Ramly, Nur (International Journal of Engineering and Technology, 2018)
A few parameters were optimized to maximize the production of Bacillus lehensis G1’s extracellular protease. The B. lehensis G1 was cultivate using the statistical method with ten different variables. These ten variables were initially screened using the Plackett-Burman design and subsequently, the significant variables were further optimized via response surface methodology. A statistical model for the effect of the four variables which includes casein, corn flour, temperature and NaCl was generated using the central composite design (CCD). The result showed that the production rate of the extracellular protease was twenty-fold higher when compared to the reference medium. These experimental data showed that casein and temperature give a positive and negative effect on protease production, respectively.